Presenting signs and patient co-variables in Gaucher disease: outcome of the Gaucher Earlier Diagnosis Consensus (GED-C) Delphi initiative - Mehta, Atul (2019)
Background: Gaucher disease (GD) presents with a range of signs and symptoms. Physicians can fail to recognise the early stages of GD owing to a lack of disease awareness, which can lead to significant diagnostic delays and sometimes irreversible but avoidable morbidities. Aim: The Gaucher Earlier Diagnosis Consensus (GED-C) initiative aimed to identify signs and co-variables considered most indicative of early type 1 and type 3 GD, to help non-specialists identify ‘at-risk’ patients who may benefit from diagnostic testing. Methods: An anonymous, three-round Delphi consensus process was deployed among a global panel of 22 specialists in GD (median experience 17.5 years, collectively managing almost 3000 patients). The rounds entailed data gathering, then importance ranking and establishment of consensus, using 5-point Likert scales and scoring thresholds defined a priori. Results: For type 1 disease, seven major signs (splenomegaly, thrombocytopenia, bone-related manifestations, anaemia, hyperferritinaemia, hepatomegaly and gammopathy) and two major co-variables (family history of GD and Ashkenazi-Jewish ancestry) were identified. For type 3 disease, nine major signs (splenomegaly, oculomotor disturbances, thrombocytopenia, epilepsy, anaemia, hepatomegaly, bone pain, motor disturbances and kyphosis) and one major co-variable (family history of GD) were identified. Lack of disease awareness, overlooking mild early signs and failure to consider GD as a diagnostic differential were considered major barriers to early diagnosis. Conclusion: The signs and co-variables identified in the GED-C initiative as potentially indicative of early GD will help to guide non-specialists and raise their index of suspicion in identifying patients potentially suitable for diagnostic testing for GD.